ASSESSING GILLETTE ONLINE ADVERTISING BACKLASH IN QUORA USING NETNOGRAPHY - Sulianta, Feri (CENTRAL ASIA AND THE CAUCASUS, 2022)
The advertisement with the theme "The Best Men Can Be" is an advertising campaign for the Gillette brand with social nuances carried out by the company Procter & Gamble. The campaign was aired online on January 13, 2019 in the form of a short film entitled We Believe: The Best Men Can Be. The release of this short film became controversy and negative response by various online commentators, and became one of the most disliked videos on YouTube. In addition, various news portals and personal blogs also discussed the impact of Gilllete's advertisements. To reveal the perspective of a certain audience that represents people's thoughts and opinions as a whole proportionally, then in this case Quora can be used as a social site for netnographic research about the Gilette controversial ad case.